INDUKSI EMBRIO SOMATIK Shorea pinanga Scheff. PADA KONDISI FISIK MEDIA BERBEDA - Yelnititis Yelnititis (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
Shorea pinanga (Scheff.) is a member of Dipterocarpaceae which has an important role both as a forest timber and also non forest timber product (tengkawang). The purpose of this experiment is to obtain the best treatment for somatic embryos formation. Friable callus was used as explants whereas liquid and solid MS media supplemented with vitamin B, 30 g/l sucrose were used as basal medium. Embryogenic callus was induced through three times subcultured in basal medium with 5.0 mg/l 2,4- D. Somatic embryo was induced using 100 mg of embryogenic callus with the addition of 0.5, 1.0, and 1.5 mg/l kinetin. The observation was done on texture, numbers and color of embryogenic callus and weekly number of somatic embryos for eight weeks. The kinetin treatment of 1.5 mg/l on liquid medium was the best treatment because it is able to induce 162 cotyledonary stage of somatic embryos for eight weeks.